Short Review: Mitigation of Current Environmental Concerns from Methanol Synthesis - Andrew Young; Der-Jong Dai; Ho-Shing Wu; Donny Lesmana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Methanol has become a widely used and globally distributed product. Methanol is very important due to the current depletion of fossil fuels. Industrially, methanol produced from the catalytic reaction of synthetic gas composed of hydrogen, carbon monoxide, and carbon dioxide. Methanol production has brought great attention due to carbon dioxide as the main source of greenhouse gas emissions. Combined of reducing CO2 emissions and supplying an alternative fuel source has created the idea of a carbon neutral cycle called “the methanol economy”. The best catalyst for the methanol economy would show a high CO2 conversion and high selectivity for methanol production. This paper investigates research focused on catalyst development for efficient methanol synthesis from hydrogenation of carbon dioxide through added various supports and additives such as silica, zirconium, and palladium. Catalysts that displayed the highest activity included a zirconia and silicon-titanium oxide promoted Cu/Zn/Al2O3 catalyst. Alternative method of catalyst preparation, include the oxalate-gel, solid-state reaction, co-precipitation and combustion method also investigated. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)